Chronic pain induces nociceptive neurogenesis in dorsal root ganglia from Sox2‐positive satellite cells. Issue 6 (16th January 2019) - Zhang, Li; Xie, Rougang; Yang, Jiping; Zhao, Youyi; Qi, Chuchu; Bian, Ganlan; Wang, Mengmeng; Shan, Junjia; Wang, Chen; Wang, Dong; Luo, Ceng; Wang, Yazhou; et al.
Abstract: Chronic pain is one of the most prevalent chronic diseases in the world. The plastic changes of sensory neurons in dorsal root ganglia (DRG) have been extensively studied as the underlying periphery mechanism. Recent studies revealed that satellite cells, the major glial cells in DRG, also played important roles in the development/modulation of chronic pain. Whether DRG satellite glial cells generate new neurons as their counterparts in enteric nerve ganglia and carotid body do under pathological conditions remains poorly investigated. Here, we report that chronic pain induces proliferation and upregulation of progenitor markers in the sex‐determining region Y‐box 2 (Sox2)‐ and platelet‐derived growth factor receptor alpha (PDGFRα)‐positive satellite glial cells. BrdU incorporation assay revealed the generation of IB4‐ and CGRP‐positive neurons, but not NF200‐positive neurons in DRG ipsilateral to injury. Genetic fate tracings showed that PDGFRα‐positive cells did not generate neurons, whereas Sox2‐positive cells produced both IB4‐ and CGRP‐positive neurons. Interestingly, glial fibrillary acidic protein‐positive cells, a subpopulation of Sox2‐positive satellites, only gave birth to IB4‐positive neurons. Local persistent delivery of tetrodotoxin to the sciatic nerve trunk significantly reduced the pain‐induced neurogenesis. Furthermore, patch‐clamp studies demonstrated that these glia‐derived new neurons could fire action potentials and respond to capsaicin. Taken together, our data demonstrated a chronic pain‐induced nociceptive neurogenesis in DRG from Sox2‐positive satellite cells, indicating a possible contribution of DRG neurogenesis to the pathology of chronic pain. Main Points: Chronic pain activates satellite glial cells and induces nociceptive neurogenesis in ipsilateral DRG. PDGFRα+ cells in DRG are gliogenic under chronic pain. Sox2+ cells are the major neurogenic cells in DRG under chronic pain.